2011
DOI: 10.1007/s00266-010-9649-9
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Frown Lines with an Endoscopic Forehead Lift Procedure (Corrugator Muscle Disinsertion)

Abstract: Disinsertion of the corrugator supercilli, procerus, or orbicularis oculi muscles can decrease contractility with less chance of damaging nearby or intermingled sensory nerves than offered by resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Among these, glabellar lines are perceived as obvious sign of aging and individuals with glabellar lines often seek treatment because these wrinkles can deliver erroneous impression of being annoyed or angry [11]. Currently, there are various methods used to treat these wrinkles, including surgery, botulinum toxin A (BXTA), and implants [11,12]. Accumulating evidence based on clinical trials has indicated that BXTA is an effective and safe aesthetic treatment method for glabellar lines [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, glabellar lines are perceived as obvious sign of aging and individuals with glabellar lines often seek treatment because these wrinkles can deliver erroneous impression of being annoyed or angry [11]. Currently, there are various methods used to treat these wrinkles, including surgery, botulinum toxin A (BXTA), and implants [11,12]. Accumulating evidence based on clinical trials has indicated that BXTA is an effective and safe aesthetic treatment method for glabellar lines [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…Corrugator muscle excision (using endoscopic alligator forceps) and incision (cutting although the body of muscle) were initially the procedure of choice. Since a few patients developed postoperative glabellar depression, the technique was changed in muscle disinsertion 17 (see Video, Supplemental Digital Content 6, available at http://links.lww.com/IOP/A297, which demonstrates corrugator muscle disinsertion) and simultaneous fat globule graft (see Video, Supplemental Digital Content 7, available at http:// links.lww.com/IOP/A298, which demonstrates fat graft). The graft helps replace the volume and prevent the corrugator muscle readhesion.…”
Section: Methodsmentioning
confidence: 99%
“…21 Many other studies reported the ability of the subperiosteal surgical plane to allow full dissection and receive a durable and suitable lifting effect. [22][23][24][25] However, in our surgery without lifting devices or fixation sutures, if dissection occurred on the subperiosteal plane, the surgeon should break the firm periosteum before getting to the target muscles, which had unnecessary risks and extra operation time. Hence, we bluntly dissected the surface between the frontalis muscle and the periosteum, making it easier to process these muscles directly with clean and safe surgical methods.…”
Section: Two Innovative Steps In Surgical Proceduresmentioning
confidence: 99%